Time Unbound: Framing Encounters for Embodied Connection and Ecological Imagination. (2nd October 2022) - Coats, Cala; Singha, Shagun; Zuiker, Steven; Riske, Amanda K.
Abstract : In this article, we explore the implementation of a time-based intervention in a garden-based science, technology, engineering, art, and mathematics curriculum with a 3rd-grade science class that flipped the overdetermined functions of time and overdependence on predetermined learning outcomes to cultivate a disposition of sensitivity to the environment. We concentrate on a single class session in which we bracketed brief moments of focus on the perception of sounds and smells to foster ecological attunement, prioritizing students' embodied and local knowledge. By analyzing the resulting observations and discussions, we describe how the timed exercises activated intervals of possibility for ecological connection, registered through expressions of curiosity and wonder, where a spectrum of imaginative potential emerged. In the findings, we also discuss unexpected tensions that emerged between the educators' desire to manage classroom behavior and generate identifiable data while also intending to embrace ambiguity in a playful and imaginative atmosphere.